How Learners Perceive Inter-Disciplinary Dialogic Science Related Learning Experiences: A Mixed-Method Study - Aviv Sharon; Lihi Telem; Einat Heyd-Metzuyanim (Karolinum Press, 2024)
Well-designed, dialogic, and interdisciplinary learning opportunities in science related disciplines can promote many educational goals. The difficulty lies in providing these opportunities in schools. Can out-of-school focus days fill the void? Here, we performed a mixed methods study to discover how middle school learners perceive focus days that included dialogic, interdisciplinary activities in mathematics, science, and philosophy, all around socio-scientific dilemmas. We also sought to understand the experiences' impact on learners' self-perceived dialogic engagement in the school classroom. We focused on (1) learners' perceptions and recollections of the dialogic climate during the focus days; (2) the perceived contribution of the three disciplines (mathematics, science and philosophy) to the interdisciplinary focus days; and (3) the focus days' effects on the dialogic climate in the everyday school environment. Our findings suggest that (1) learners generally considered the focus days as enjoyable and different than their everyday school experience; (2) students did not consider each discipline equally relevant to the focus days' main topics; and (3) the effects of the focus days were localized, that is, no impact was found on the dialogic climate at school. We discuss implications for promoting interdisciplinary, dialogic science related learning in secondary schools.